2010 IEEE International Ultrasonics Symposium 2010
DOI: 10.1109/ultsym.2010.5935909
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the subharmonic emission from microbubbles using linear and nonlinear frequency modulated signals

Abstract: Universities of LeedsAbstract-In medical ultrasound imaging, coded excitation is widely used to increase signal to noise ratio (SNR) and penetration without increasing the peak pressure level by using longer pulse durations. The aim of this work is to utilize chirp coded excitation and investigate the effect on subharmonic emission from contrast agents for nondestructive subharmonic imaging. The subharmonic emission of the microbubbles is measured as a function of pressure and bandwidth for linear frequency mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The excitation center frequency was selected as 7.6 MHz, since it was double the resonance frequency of the microbubbles used in this study. Instead of comparing the peak subharmonic power or subharmonic-to-fundamental ratio, which are commonly used for characterizing microbubbles and for measuring their nonlinear behaviors [48], [50], [51], the total subharmonic power was calculated to evaluate the subharmonic behavior of UCAs to different excitation signals. The reason for using this method was due to the variation in bandwidths of the LFM and NLFM chirps used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excitation center frequency was selected as 7.6 MHz, since it was double the resonance frequency of the microbubbles used in this study. Instead of comparing the peak subharmonic power or subharmonic-to-fundamental ratio, which are commonly used for characterizing microbubbles and for measuring their nonlinear behaviors [48], [50], [51], the total subharmonic power was calculated to evaluate the subharmonic behavior of UCAs to different excitation signals. The reason for using this method was due to the variation in bandwidths of the LFM and NLFM chirps used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the excitation bandwidth of a fixed duration signal was spread the signal's energy to a wider spectral range and increased the likelihood of subharmonic generation from a polydisperse population of microbubbles [48]. Increasing the signal's total energy by using a different amplitude modulation also improves the subharmonic response from UCAs.…”
Section: A Subharmonic Generation With Lfm and Nlfmmentioning
confidence: 99%
“…Nevertheless, out of the presented nonlinear methods, many research works demonstrated the benefit of subharmonic analysis when microbubbles, therefore porosity, are considered [ 53 , 65 , 66 , 67 , 68 , 69 , 70 ]. A generic amplitude spectrum of an acquired filtered backscattered signal can be presented as shown in Figure 3 .…”
Section: Nonlinear Ultrasound Approachmentioning
confidence: 99%
“…Among them, nonlinear elastic wave spectroscopy (NEWS) [ 40 , 41 , 42 ], nonlinear elastic wave modulation spectroscopy (NEWMS) [ 43 , 44 , 45 ], nonlinear imaging methods [ 46 , 47 , 48 ], and phase symmetry analysis (PSA) techniques [ 49 , 50 ] were used to explicitly interrogate the nonlinear behaviour of the medium and its effect on wave propagation. Many studies have shown that nonlinearities are generated in structures in the presence of ruptures, voids, cohesive bonds, and the opening/closing of surfaces or micro-cracks [ 51 , 52 , 53 ]. Material nonlinearity of damaged regions, in terms of nonlinear harmonic generation (due to ultrasound excitation), has been widely used over the past few years as a reliable signature for material flaw detection in both metallic and composite structures [ 46 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…therefore, care must be taken in choosing the optimum number of cycles). In addition this technique combined with nonlinear frequency modulated ultrasound signals (Harput et al 2010) will further improve the signal to noise and resolution.…”
Section: Possible Applications Of the Observed Phenomenonmentioning
confidence: 99%